Analysis of Physical Properties of Well Water Quality in Pasuruhan Kidul Kudus Village - Fariyya, Dewi Raokhil Iklima; Yulianti, Ian; Fianti, Fianti (Physics Communication, 2021)
Water is a natural resource that is very important for human life and other creatures. Water is used to meet various needs, including bathing, drinking, cooking, and washing. This study aimed to determine the quality of healthy water in the village of Pasuruhan Kidul Jati Kudus. One of the parameters measured for hygiene sanitation is a physical parameter. Measurement of physical parameters is the first step in analyzing water quality. In this study, several physical parameters were used to determine water quality, including temperature, turbidity, color, Total Dissolved Solid (TDS), taste, smell, and pH. This research was conducted for 7 days in three different places: home, mosque, and school. The method used in this research is to analyze the water quality of wells, mosques, and schools in Pasuruan Kidul Village. The results showed that the temperature values in the three places were around 29.4-29.6°C, the turbidity of the three places was 1 NTU, the water in all places was colorless, tasteless, odorless, the value of Total Dissolved Solid (TDS) at the three places the value is around 412.8-418.4 (mg/l), and the pH is 7.4 so that the water quality in the three places is below the maximum water quality standard threshold.